Developement of electrical equivalent circuit for super capacitor - Muhammad Bukhari Amiruddin. (2011)
Over decades, capacitors had played a major role among electronic circuits and system. However, in recent years, the future of Super Capacitor to replace our present energy storage elements such as batteries and conventional capacitors had been promising. As of present, there are many different types of electrical models, and most of them are derived from the observed charging and discharging behavior, without considering the actual underlying physical and chemical processes during the charging and discharging. In this project, a physics based equivalent circuit will be proposed which will also include an understanding of the physical and chemical processes during the charging and discharging. The explanation of the various observed electrical behavior of the super capacitors will be given from this equivalent circuit model, and the model will be used to examine the various measurement results reported in the literature.